DETERMINANTS OF STUNTING IN CHILDREN AGED 24-59 MONTHS IN THE KASREMAN COMMUNITY HEALTH CENTER - Kesumawati, Devi; Hidayah, Nurul (Universitas Airlangga, 2020)
Introduction: In Indonesia stunting still the main problem and concern in the field of nutrition, this condition in mark with height not according to age measured use the z-score. Children said stunting if the z-score <- 2SD until â‰¥- 3 SD and very short if < - 3 SD. Methods: This study to attemps to analyze the determinant. Stunting using study correlation with case design study case control done measurements on past (retrospektif) 38 group with the total sample case and 38 respondents. Results: The control group thr kind of data used primary data. Respondents who experienced anemia is 20 and 15 respondents (39,5 %) have children stunting and 5 responden (13,5 %) has a normal, with p-value p= 0,019 (p < 0,005) showing there the relationship between the anemia as the stunting in the work area Puskesmas Kasreman Conclusion: The conclusion of research is several factors such in minutely in the work area Puskesmas Kasreman, risk heving the anemia higher have children stunting. Expected health service, parents and knowledge of the factor causing people to stunting to prevent the occurrence stunting